HISTORY OF DISTRIBUTION AND DEVELOPMENT OF CARPET PRODUCTION IN PEASANT FARMS OF SLOBID UKRAINE - Трубчанінов, Микола (SWorldJournal, 2024)
In Slobid Ukraine, carpets were used by all strata of the population. They were widely used by the ruling classes. The main emphasis of the article is on the technique of production and dyeing of carpets in the Slobozhan region at the end of the 18th and